ALTERATIONS IN THE CENTRAL DOGMA UNITS UNDER TRIVALENT ARSENIC STRESS DURING PREPARATORY PHASE OF OVARIAN CYCLE OF MYSTUS (M.) VITTATUS (BL.) - and J.P. Shukla, Anuradha Shukla, Yogendra Kumar Payasi (Journal of Advanced Zoology, 2022)
Central dogma units comprise of DNA, RNA and synthesis of protein. Reproductive cycle in fishes is always dynamic and the units of central dogma are always changing in different phases of testicular and ovarian cycle which constitute reproductive cycle in fishes. The adult specimens of Mystus (M.) vittatus, a tropical siluroid, when exposed for 30 days to sublethal concentration of trivalent arsenic (11.24 mg/I) revealed significant decline in DNA, RNA and consequently protein in the ovary of Mystus (M.) vittatus during its preparatory phase. However, 15 days exposure revealed less significant alterations. Causes for declining in various units of central dogma and consequently protein synthesis is discussed in this paper.